Co9S8 / CoOOH-coated NF self-supporting electrode and preparation method thereof

By preparing Co9S8/CoOOH@NF self-supporting electrodes by hydrothermal reaction and chemical oxidation reconstruction methods on a foam nickel substrate, the problem of low efficiency of existing non-precious metal-based redox catalysts is solved, and efficient redox performance is achieved.

CN119593002APending Publication Date: 2025-03-11ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411694037.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing non-precious metal-based redox catalysts are inefficient in electrocatalytic oxygen evolution reactions and are limited by electron conductivity and intrinsic activity.

Method used

Co9S8 precursors are grown on the foam nickel substrate by hydrothermal reaction, and then immersed in hydrogen peroxide solution, and prepared Co9S8/CoOOH@NF self-supporting electrodes by chemical oxidation and reconstruction.

Benefits of technology

A heterogeneous interface of crystalline amorphous state was constructed, providing a large number of active sites and intrinsic electric fields, enhancing the conductivity of electrons, and significantly improving the redox performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593002A_ABST
    Figure CN119593002A_ABST
Patent Text Reader

Abstract

The invention discloses a Co9S8 / CoOOH-coated NF self-supporting electrode and a preparation method thereof, and the method comprises the following steps: growing a Co9S8 precursor on an NF substrate through a hydrothermal reaction, then soaking the Co9S8 precursor in a hydrogen peroxide solution, and preparing the Co9S8 / CoOOH-coated NF self-supporting electrode through a chemical oxidation reconstruction mode. The technological process is simple and rapid, the prepared electrode is large in specific surface area, high in conductivity and multiple in electrochemical active sites, compared with an electrode of a traditional structure, the electrode is simple, efficient and excellent in performance, the defects that a traditional catalyst is complex in preparation technological process and common in performance are effectively overcome, and the application prospect is wide. The problems that in the water oxidation process, OER has a high thermodynamic potential barrier, and high potential is needed to drive overall water decomposition are solved, and the method has great application value in the field of electrochemical catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic electrode preparation, and in particular to a Co9S8 / CoOOH@NF self-supporting electrode and a preparation method thereof. Background Art

[0002] The electrocatalytic oxygen evolution reaction (OER) is an important half-reaction in many renewable energy conversion and storage technologies, such as water splitting, CO2 reduction, nitrogen fixation, and metal-air batteries. However, the efficiency of OER is often limited by sluggish kinetics, which involves multiple proton-coupled electron transfers. Although noble metal-based catalysts such as IrO2 and RuO2 exhibit good OER activity, their scarcity and high cost hinder widespread application. Therefore, much effort has been invested in the development of non-noble metal-based OER catalysts, such as metal oxides, phosphides, nitrides, selenides, and sulfides.

[0003] Among them, cobalt-based sulfide catalysts have been widely studied due to their low cost, nontoxicity, and considerable electrocatalytic activity. However, their catalytic performance is still limited by poor electronic conductivity and mediocre intrinsic activity. Summary of the invention

[0004] The object of the present invention is to provide a Co9S8 / CoOOH@NF self-supporting electrode and a preparation method thereof, wherein the preparation process is simple and rapid, and the prepared electrode has a large specific surface area, high electrical conductivity, and a large number of electrochemically active sites.

[0005] In one aspect of the present invention, the present invention provides a method for preparing a Co9S8 / CoOOH@NF self-supporting electrode. According to an embodiment of the present invention, a Co9S8 precursor is grown on a nickel foam substrate by a hydrothermal reaction, and then immersed in a hydrogen peroxide solution to prepare a Co9S8 / CoOOH@NF self-supporting electrode by chemical oxidation reconstruction.

[0006] In addition, the method for preparing a Co9S8 / CoOOH@NF self-supporting electrode according to the above embodiment of the present invention may also have the following additional technical features:

[0007] In some embodiments of the present invention, the method comprises the following steps:

[0008] (1) placing the nickel foam substrate in a hydrochloric acid solution and ultrasonicating it, placing it in an ethanol solution and ultrasonicating it again after rinsing it, taking it out and rinsing it again to obtain a clean nickel foam substrate;

[0009] (2) adding deionized water, CH4N2S and Co(NO3)2·6H20 into a hydrothermal reactor, stirring to obtain a uniformly mixed solution, placing the foamed nickel substrate therein, taking out and drying after the hydrothermal reaction to obtain a Co9S8@NF precursor;

[0010] (3) The dried Co9S8@NF precursor was immersed in a H2O2 solution and then air-dried to obtain a Co9S8 / CoOOH@NF self-supporting electrode.

[0011] In some embodiments of the present invention, in step (1), the size of the nickel foam substrate is 3-4 cm in length and 2.5-3.5 cm in width, the concentration of the hydrochloric acid solution is 0.5-2.5 mol / L, the ultrasonic time is 20-80 minutes, the rinsing is carried out with deionized water, and the number of rinsing is 1-6 times.

[0012] In some embodiments of the present invention, in step (2), the concentration of CH4N2S is 0.03-0.09 mol / L, and the concentration of Co(NO3)2·6H20 is 0.01-0.04 mol / L.

[0013] In some embodiments of the present invention, in step (2), the temperature of the hydrothermal reaction is 120-180° C., and the time of the hydrothermal reaction is 8-14 h.

[0014] In some embodiments of the present invention, in step (2), the drying temperature is 20-80° C., and the drying time is 1-3 h.

[0015] In some embodiments of the present invention, in step (3), the mass fraction of H2O2 is 5%-30%, and the soaking treatment time is 20-100 min.

[0016] In another aspect of the present invention, the present invention proposes a preparation method as mentioned above to prepare a Co9S8 / CoOOH@NF self-supporting electrode.

[0017] In addition, the Co9S8 / CoOOH@NF self-supporting electrode according to the above embodiment of the present invention may also have the following additional technical features:

[0018] In some embodiments of the present invention, the Co9S8 / CoOOH@NF self-supporting electrode is an ultra-thin nanosheet array structure that is cross-linked and uniformly covered on a nickel foam substrate.

[0019] In another aspect of the present invention, the present invention proposes an application of a Co9S8 / CoOOH@NF self-supporting electrode in oxygen evolution reaction by water electrolysis.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The present invention adopts an oxidation reconstruction strategy. Through the strong oxidation performance of hydrogen peroxide, part of the lattice-ordered Co9S8 is oxidized and reconstructed into an amorphous phase of CoOOH, forming a crystalline amorphous heterogeneous interface. The numerous dangling bonds and abundant unsaturated surface atoms generated by constructing the heterogeneous interface provide a large number of adsorption sites for reactants. At the same time, the coordination of surface atoms is highly unsaturated, which will produce abundant defects / vacancies and provide a large number of active sites for electrocatalysis. At the same time, the construction of a crystalline amorphous heterogeneous interface will generate an intrinsic electric field, accelerate charge transfer, thereby greatly enhancing the electronic conductivity, and ultimately greatly improving the OER performance.

[0022] 2) The Co9S8 / CoOOH@NF self-supporting electrode prepared in the present invention is an ultra-thin nanosheet array structure, which is cross-linked and evenly covered on the NF, has a very large specific surface area, and has micropores on the surface, which expand the effective surface area of ​​the electrochemical reaction of the catalyst, facilitate the effective contact between the electrolyte and the catalyst, thereby improving the electrocatalytic efficiency.

[0023] 3) Compared with electrodes of traditional structures, the present invention is simple and efficient, effectively overcoming the shortcomings of traditional catalyst preparation processes that are complex and have average performance, and solving the problem that OER has a high thermodynamic barrier during water oxidation and requires a high potential (>1.23V) to drive overall water decomposition. It has great application value in the field of electrochemical catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The SEM images of the Co9S8 / CoOOH@NF self-supporting electrode at different magnifications in Example 1 of the present invention, a is 200nm, b is 500nm, and c is 1μm;

[0025] Figure 2 TEM image of the Co9S8 / CoOOH@NF self-supporting electrode in Example 1 of the present invention;

[0026] Figure 3 HRTEM image of the Co9S8 / CoOOH@NF self-supporting electrode in Example 1 of the present invention;

[0027] Figure 4 Electrocatalytic performance of the electrodes prepared in Example 1 and Comparative Examples 1-3 of the present invention for OER, wherein Co9S8 / CoOOH@NF, Co9S8@NF, RuO2@NF and NF were evaluated for OER activity by linear sweep voltammetry at a scan rate of 5 mV / s in 1 M KOH;

[0028] Figure 5 EIS graphs of electrodes prepared in Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The NF (nickel foam) used in the following examples and comparative examples is 1 mm thick, 200 mm wide, and 1 m long, and was purchased from Taobao Cyber ​​Electrochemical Materials Network. The electrochemical test was performed using a CHI660E electrochemical workstation.

[0031] Example 1

[0032] A method for preparing a Co9S8 / CoOOH@NF self-supporting electrode comprises the following steps:

[0033] (1) The NF substrate for the experiment was cut into pieces of 3.7 cm in length and 3 cm in width. The NF substrate was placed in a 60 ml solution of hydrochloric acid and deionized water in a volume ratio of 1:5 and ultrasonicated for 40 minutes, and then rinsed with deionized water for 3 times. The NF substrate was then placed in a 40 ml ethanol solution and ultrasonicated for 40 minutes again. After being taken out, it was rinsed with deionized water again for 3 times.

[0034] (2) In a 100 ml hydrothermal reactor, 40 ml of deionized water, 221 mg of CH4N2S and 291 mg of Co(NO3)2·6H20 were added and stirred for 1 h to obtain a uniformly mixed solution. The cleaned NF substrate was placed in the above solution, hydrothermally heated at 160 °C for 12 h, and then taken out and dried in an oven at 60 °C for 2 h to obtain the Co9S8@NF precursor.

[0035] (3) The Co9S8@NF precursor was immersed in 40 ml of a 30 wt% hydrogen peroxide solution for 60 min, and then naturally air-dried to obtain a Co9S8 / CoOOH@NF self-supporting electrode.

[0036] The Co9S8 / CoOOH@NF prepared in this example was subjected to scanning electron microscopy (SEM) analysis. The SEM image is shown in Figure 1 As shown, the electrocatalyst material of the present invention has an ultra-thin nanosheet array structure, which is cross-linked and uniformly covered on the NF, has a very large specific surface area, and has micropores on the surface, which expand the effective surface area of ​​the electrochemical reaction of the catalyst, facilitate the effective contact between the electrolyte and the catalyst, and accelerate the electron transfer process.

[0037] An appropriate amount of Co9S8 / CoOOH was scraped from Co9S8 / CoOOH@NF and tested by high-resolution transmission electron microscopy (TEM). Figure 2 and Figure 3 As shown. Figure 2 It can be further proved that Co9S8 / CoOOH@NF has an ultrathin nanosheet structure. Figure 3 This indicates that Co9S8 / CoOOH@NF has a crystalline-amorphous heterointerface, which produces abundant defects / vacancies and provides a large number of active sites for electrocatalysis, thus greatly improving the OER performance.

[0038] Example 2

[0039] A method for preparing a Co9S8 / CoOOH@NF self-supporting electrode comprises the following steps:

[0040] (1) The NF substrate for the experiment was cut into pieces of 4 cm in length and 3 cm in width. The NF substrate was placed in a 60 ml solution of hydrochloric acid and deionized water in a volume ratio of 1:11 and ultrasonicated for 30 minutes, and then rinsed with deionized water twice. The NF substrate was then placed in a 50 ml ethanol solution and ultrasonicated again for 30 minutes. After being taken out, it was rinsed with deionized water again twice.

[0041] (2) Add 50 ml of deionized water, 235 mg of CH4N2S and 311 mg of Co(NO3)2·6H20 into a 100 ml hydrothermal reactor and stir for 1 h to obtain a uniformly mixed solution. Place the cleaned NF substrate in the above solution, hydrothermally heat at 160 °C for 12 h, then take it out and dry it in an oven at 60 °C for 2 h to obtain the Co9S8@NF precursor.

[0042] (3) The Co9S8@NF precursor was immersed in 30 ml of 30 wt% hydrogen peroxide solution for 40 min, and then naturally air-dried to obtain the Co9S8 / CoOOH@NF self-supporting electrode.

[0043] Comparative Example 1

[0044] The Co9S8@NF self-supporting electrode of this comparative example is different from that of Example 1 only in that there is no step (3), that is, the Co9S8@NF self-supporting electrode is obtained after drying in an oven in step (2).

[0045] Comparative Example 2

[0046] The preparation method of the RuO2@NF electrocatalyst of this comparative example comprises the following steps:

[0047] Weigh 10 mg of RuO2 and dissolve it in 750 ml of deionized water and 250 ml of isopropanol. Ultrasonicate for 40 min, add 5 ml of Nafion solution, and ultrasonicate for another 40 min. Apply the above solution evenly on a clean NF with a length of 1.5 cm and a width of 1 cm. The loading amount is about 1 mg cm -2 .

[0048] Comparative Example 3

[0049] This comparative example is the NF blank control group. The NF substrate was placed in a 60 ml solution of hydrochloric acid and deionized water in a volume ratio of 1:5 and ultrasonicated for 40 minutes, and then rinsed with deionized water for 3 times; then the NF substrate was placed in a 40 ml ethanol solution and ultrasonicated again for 40 minutes, and then taken out and rinsed with deionized water for 3 times, and finally cut into pieces with a length of 1.5 cm and a width of 1 cm.

[0050] Electrochemical performance tests were performed on the electrodes of Example 1 and Comparative Examples 1-3. Electrochemical measurements were performed on an electrochemical workstation (CHI660E) using a standard three-electrode system. The electrodes of Example 1 and Comparative Examples 1-3 were directly used as working electrodes (the effective contact area of ​​the tested solution was 1×1 cm 2 ). The electrochemical properties of the catalysts were tested using a standard three-electrode system at room temperature and pressure. The platinum electrode was used as the counter electrode, the Ag / AgCL electrode was used as the reference electrode, and the electrolytes were freshly prepared 1.0 M KOH solutions.

[0051] Depend on Figure 4 It can be seen that the catalytic material of Experimental Example 1 has a current density of 100 mA·cm -2 The oxygen evolution overpotential in alkaline electrolyte (1.0 M KOH) is 397 mV, indicating that it has extremely low overpotential and strong OER performance. -2 When the oxygen evolution overpotential in alkaline electrolyte (1.0 M KOH) is 437 mV, the catalytic material of comparative example 2 has a current density of 100 mA cm -2 When the oxygen evolution overpotential in alkaline electrolyte (1.0 M KOH) is 677 mV, the catalytic material of comparative example 3 has a current density of 100 mA cm -2 The oxygen evolution overpotential in an alkaline electrolyte (1.0 M KOH) is 797 mV.

[0052] The electrodes of Example 1 and Comparative Examples 1-3 were subjected to electrochemical impedance spectroscopy (EIS) tests, and the test parameters were: AC amplitude of 5 mV, frequency range of 0.01-10 5 Hz.

[0053] Depend on Figure 5It can be seen that after H2O2 treatment, the impedance of the Co9S8 / CoOOH@NF precursor of Experimental Example 1 is greatly reduced compared with Comparative Examples 1-3, indicating that the Co9S8 / CoOOH@NF precursor of Experimental Example 1 has an ultra-thin structure and thus has extremely high electrical conductivity, which undoubtedly greatly enhances the transmission efficiency of four electrons in the OER process, thereby greatly enhancing the electrocatalytic OER performance.

[0054] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a Co9S8 / CoOOH@NF self-supporting electrode, characterized in that: The Co9S8 precursor was grown on the nickel foam substrate by hydrothermal reaction, and then immersed in hydrogen peroxide solution to prepare the Co9S8 / CoOOH@NF self-supporting electrode by chemical oxidation reconstruction.

2. The method for preparing a Co9S8 / CoOOH@NF self-supporting electrode according to claim 1, characterized in that: The following steps are involved: (1) placing the nickel foam substrate in a hydrochloric acid solution and ultrasonicating it, placing it in an ethanol solution and ultrasonicating it again after rinsing it, taking it out and rinsing it again to obtain a clean nickel foam substrate; (2) adding deionized water, CH4N2S and Co(NO3)2·6H20 into a hydrothermal reactor, stirring to obtain a uniformly mixed solution, placing the foamed nickel substrate therein, taking out and drying after the hydrothermal reaction to obtain a Co9S8@NF precursor; (3) The dried Co9S8@NF precursor was immersed in a H2O2 solution and then air-dried to obtain a Co9S8 / CoOOH@NF self-supporting electrode.

3. The method for preparing a Co9S8 / CoOOH@NF self-supporting electrode according to claim 2, characterized in that: In step (1), the size of the nickel foam substrate is 3-4 cm in length and 2.5-3.5 cm in width, the concentration of the hydrochloric acid solution is 0.5-2.5 mol / L, the ultrasonic time is 20-80 minutes, the rinsing is performed with deionized water, and the number of rinsing is 1-6 times.

4. The method for preparing a Co9S8 / CoOOH@NF self-supporting electrode according to claim 2, characterized in that: In step (2), the concentration of CH4N2S is 0.03-0.09 mol / L, and the concentration of Co(NO3)2·6H20 is 0.01-0.04 mol / L.

5. The method for preparing a Co9S8 / CoOOH@NF self-supporting electrode according to claim 2, characterized in that: In step (2), the temperature of the hydrothermal reaction is 120-180° C., and the time of the hydrothermal reaction is 8-14 h.

6. The method for preparing a Co9S8 / CoOOH@NF self-supporting electrode according to claim 2, characterized in that: In step (2), the drying temperature is 20-80° C., and the drying time is 1-3 hours.

7. The method for preparing a Co9S8 / CoOOH@NF self-supporting electrode according to claim 2, characterized in that: In step (3), the mass fraction of H2O2 is 5%-30%, and the soaking treatment time is 20-100 min.

8. A Co9S8 / CoOOH@NF self-supporting electrode prepared by the preparation method of the Co9S8 / CoOOH@NF self-supporting electrode according to any one of claims 1 to 7.

9. A Co9S8 / CoOOH@NF self-supporting electrode according to claim 8, characterized in that: The Co9S8 / CoOOH@NF self-supporting electrode is an ultra-thin nanosheet array structure that is cross-linked and evenly covered on a nickel foam substrate.

10. Use of the Co9S8 / CoOOH@NF self-supporting electrode according to claim 8 in oxygen evolution reaction by water electrolysis.